THE HISTORY OF THE DEVELOPMENT OF BUKHARA MAQOM OF EXECUTIVE POWER - Ergashev Ramziddin Rakhimovich (International Journal on Integrated Education, 2023)
The article examines the origins and processes of the formation of Bukhara shashmaqoms, the place of their status in oriental music, and their original theoretical foundations. When studying the theoretical foundations of maqam, the emphasis is mainly on the theory of ilmi iiko (rhythm).